2007
DOI: 10.4049/jimmunol.179.1.80
|View full text |Cite
|
Sign up to set email alerts
|

Disparate Primary and Secondary Allospecific CD8+ T Cell Cytolytic Effector Function in the Presence or Absence of Host CD4+ T Cells

Abstract: The role of CD4+ T cells in promoting CD8+ T cell effector activity in response to transplant Ags in vivo has not been reported. We used a hepatocellular allograft model known to initiate both CD4-dependent and CD4-independent rejection responses to investigate the contribution of CD4+ T cells to the development, function, and persistence of allospecific CD8+ T cell effectors in vivo. Complete MHC-mismatched hepatocellular allografts were transplanted into C57BL/6 (CD4-sufficient) or CD4 knockout (CD4-deficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(49 citation statements)
references
References 68 publications
5
44
0
Order By: Relevance
“…Furthermore, the of hepatocyte transplant. These studies support the idea although antigen-specific CD8 + T cells have been shown to proliferate at the graft site during combined CD4 and that alloreactive CD8 + T cells can be activated to develop potent effector function at the graft site to cause CD8-dependent rejection, as well as in (CD4-independent) CD8 dependent rejection (23). It was interesting rapid rejection, but in the absence of CD4 + T cells, the amplification of CD8 + T-cell immunity is lessened, reto note that the inflammatory infiltrate was similar for each rejection pathway, unlike published reports showsulting in low-magnitude systemic in vivo cytotoxicity activity.…”
Section: Figuresupporting
confidence: 64%
See 3 more Smart Citations
“…Furthermore, the of hepatocyte transplant. These studies support the idea although antigen-specific CD8 + T cells have been shown to proliferate at the graft site during combined CD4 and that alloreactive CD8 + T cells can be activated to develop potent effector function at the graft site to cause CD8-dependent rejection, as well as in (CD4-independent) CD8 dependent rejection (23). It was interesting rapid rejection, but in the absence of CD4 + T cells, the amplification of CD8 + T-cell immunity is lessened, reto note that the inflammatory infiltrate was similar for each rejection pathway, unlike published reports showsulting in low-magnitude systemic in vivo cytotoxicity activity.…”
Section: Figuresupporting
confidence: 64%
“…We also investigated the correlation of peripheral immune hosts (23). However, we have subsequently determined that the presence of high titer donor-reactive antibody monitoring of alloantibody, DTH, or in vivo cytotoxicity with activity of distinct rejection mechanisms, which correlates with the magnitude of in vivo cytotoxicity observed in these hosts (Horne, unpublished observation).…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Neither DST and anti-CD154 mAb-treated C57BL/6 islet 'acceptor' mice or CD4-depleted C57BL/6 islet hepatocyte cotransplant rejector mice had alloantibody in recipient serum. Prior studies demonstrate that development of allospecific cytotoxicity after allogeneic hepatocyte transplant is CD8 + T cell mediated (46). These data indicate that local activation of CD8 + T-cell-dependent cytotoxic effector responses can precipitate islet allograft damage and/or disrupt survival of islet allografts even after long-term engraftment in the liver.…”
Section: The Influence Of Local Activation Of Alloreactive Cd8mentioning
confidence: 82%